Long-Lasting Graft-Derived Donor T Cells Contribute to the Pathogenesis of Chronic Graft-versus-Host Disease in Mice - Kosugi-Kanaya, Mizuha; Ueha, Satoshi; Abe, Jun; Shichino, Shigeyuki; Shand, Francis H. W.; Morikawa, Teppei; Kurachi, Makoto; Shono, Yusuke; Sudo, Naoto; Yamashita, Ai; Suenaga, Fumiko; Yokoyama, Akihiro; et al. (Frontiers in Immunology, 2017)
Chronic graft-versus-host disease (cGVHD) is a major complication in long-term survivors of allogeneic hematopoietic stem cell transplantation (allo-HSCT). Graft-derived T cells (TG) have been implicated in the induction of cGVHD, however, the extent of their contribution to the pathogenesis of cGVHD remains unclear. Using a mouse model of cGVHD, we demonstrate that TG predominate over hematopoietic stem cell-derived T cells generated de novo (THSC) in cGVHD-affected organs such as the liver and lung even at day 63 after allo-HSCT. Persisting TG, in particular CD8+ TG, displayed an exhausted or senescent phenotype but also contained a substantial proportion of cells that had the potential to proliferate and produce inflammatory cytokines. Host-antigens indirectly presented by donor HSC-derived hematopoietic cells were involved in the maintenance of TG in the reconstituted host. Selective depletion of TG in the chronic phase of disease resulted in the expansion of THSC and thus neither the survival nor histopathology of cGVHD were ameliorated. On the other hand, THSC depletion caused activation of TG and resulted in a lethal TG-mediated exacerbation of GVHD. The findings presented here clarify the pathological role of long-lasting TG in cGVHD.